Progress of studies on phytogeography and biodiversity of the Philippines moss flora from 1991 to 2006 - Linis, Virgilio C. (Animo Repository, 2008)
Progress in the study of Philippine moss flora and its phytogeography from 1991 to 2006 is presented. Contributions made in the enhancement of muscological information in the archipelago are reviewed. Current species richness and diversity of the country are discussed. Analysis of bryogeographical affinities of Philippine mosses are updated while its origin is re-examined based on new geologic evidence and new moss records gathered from the Philippines during the period under review.